2013
DOI: 10.1074/jbc.m113.462622
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Subtilase Cytotoxin SubAB Assembly

Abstract: Background: AB 5 toxins consist of a pentameric B-subunit and a catalytic A-subunit. Results: Crystallographic data, dissociation, and intracellular trafficking of SubAB toxin are reported. Conclusion: SubAB architecture is similar to other AB 5 toxins, whereas the B-pentamer plays an important role in assembly and intracellular trafficking. Significance: The conserved hydrophobic ring in the B-pentamer supports the view that A-and B-subunits have evolved independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…1) However, in the case of autoimmune diseases or chronic inflammatory diseases, excessive and prolonged production of cytokines is a major causative agent, which leads to tissue damage, hemodynamic changes, and multiple organ failure with a wide range of clinical manifestations and complications. 2,3) Subtilase cytotoxin (SubAB), a member of the AB 5 toxin family, was identified by Paton et al in an enterohemorrhagic Escherichia coli (EHEC) O113 : H21 that was associated with an outbreak in Australia. [4][5][6] SubAB is formed by an enzymatically active A subunit with a molecular weight of 35 kDa; it cleaves host endoplasmic reticulum (ER) chaperon protein BiP and pentameric B subunit (each monomer 13 kDa) that binds to the cell surface receptor, and mediates uptake into a target cell.…”
Section: Introductionmentioning
confidence: 99%
“…1) However, in the case of autoimmune diseases or chronic inflammatory diseases, excessive and prolonged production of cytokines is a major causative agent, which leads to tissue damage, hemodynamic changes, and multiple organ failure with a wide range of clinical manifestations and complications. 2,3) Subtilase cytotoxin (SubAB), a member of the AB 5 toxin family, was identified by Paton et al in an enterohemorrhagic Escherichia coli (EHEC) O113 : H21 that was associated with an outbreak in Australia. [4][5][6] SubAB is formed by an enzymatically active A subunit with a molecular weight of 35 kDa; it cleaves host endoplasmic reticulum (ER) chaperon protein BiP and pentameric B subunit (each monomer 13 kDa) that binds to the cell surface receptor, and mediates uptake into a target cell.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the pentameric B-subunits typically contain a higher amount of β-sheets [31]. Crystal structure analyses of the functional SubAB holo-toxin complex by Le Nours et al [32] showed that this fundamental distribution of secondary structure throughout the protein complex is true for SubAB1-His. In the current study, secondary structure analyses of the separately expressed and purified SubAB subunits revealed that SubA1-His, SubA2-2-His, and SubA2-2 showed typical α-helical signals in the far-UV CD spectra ( Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the alterations were rather evenly distributed throughout the whole protein. In total, 13 amino acids throughout SubA1 were identified to be part of the interaction regions of the toxin complex [32]. None of them were different in SubA2-2-His.…”
Section: Discussionmentioning
confidence: 99%
“…Among such factors are the AB 5 toxins, which are complexes between five copies of a B subunit employed for attachment to the host plasma membrane and a single catalytic A subunit, which subverts cellular functions once the toxin complex has been internalized (Merritt and Hol, 1995). Four AB 5 families have been reported based on the function of the catalytic subunit: the Shiga toxins, which interfere with protein biosynthesis; the pertussis and cholera toxins, which affect regulation of fluid secretion; and the subtilase cytotoxins, which have a subtilisintype serine proteinase as A subunit that cleaves an endoplasmic reticulum chaperone (Beddoe et al, 2010;Le Nours et al, 2013). More recently, a fifth family was identified in diarrhea-causing strains of Escherichia coli and Citrobacter freundii, represented by toxins EcxAB and CfxAB, respectively (Jansson et al, 2010;Karasawa et al, 2002).…”
mentioning
confidence: 99%